생리용품과 화장품의 유해물질 위해평가와 관리 가이드라인 - 최용규 (The Graduate School, Ajou University, 2018)
Chapter 1 Abstract The risk assessment was conducted to identify the level of volatile organic compound (VOCs) detected from sanitary napkins marketed in and out of Korea and to check whether the detected VOCs have any harmful impact to the health of the customers. The targets of the risk assessment were 10 VOCs including benzene, toluene, xylenes, ethylbenzene, dichloromethane, chloroform, trichloroethylene, tetrachloroethylene, styrene and hexane. The risk assessment was carried out in four stages of hazard identification, hazard characterization, exposure assessment and risk characterization. In the stage of hazard identification, the physical, chemical characters and toxicity data such as cancer, reproductive and developmental toxicity of the 10 target substances were reviewed, and possible harmful effects to human bodies were examined. In the stage of hazard characterization, the reference dose (RfD) and slope factor suggested by international risk assessment organization such as United States Environmental Protection Agency (US EPA) and World Health organization (WHO) or other researches, were considered to use. In the stage of exposure assessment, systemic exposure dose (SED) was calculated to know the amount of target substances absorbed through skin when women use sanitary napkins and panty liners. The evaluation was done by making extreme and realistic scenarios which are set based on women’s usage patterns of sanitary products. The exposure factors used in the scenarios are the amount of VOCs from the products, transfer rate, skin absorption rate, number of products used in a day, used period, and body weight. According to the scenario, the exposure factors have different values for evaluation. In the stage of hazard characterization, the possibility of harmful effects to human bodies was evaluated by comparing RfD and SED which was calculated in the exposure assessment. As a result, the value of safety margin of the product whose detected VOCs were the highest among all target products was over 1, therefore the risk possibility to human bodies by the 10 VOCs is evaluated to be low. For cancer risk, all products have been evaluated as over 10-6 except 4 cloth products in the worst-case scenario. For reusable cloth products, however, it is usually washed before and after every use so that actual exposure level might be low. Hence, the risk possibility to human due to 10 VOCs is also low. Chapter 2 Abstract Nickel is the transition metal, which causes skin allergic reaction, skin rash and etc. when exposed chronically. In addition, IARC classified pure nickel into Group 1 (carcinogenic to humans) and metallic nickel in Group 2B (possibly carcinogenic to humans). Based on these toxicological data, the nickel in cosmetic products has been prohibited in Korea and EU under the cosmetic regulation. However, most marketed cosmetic products can contain traces of nickel because nickel is present naturally in the earth. Thus, technically unavoidable traces of nickel should be controlled by monitoring marketed products. Firstly, the content of nickel was analyzed by ICP-MS in 150 commercialized cosmetic products to estimate the nickel contamination level. As a result, up to 0.0039% of nickel was contained in eye make-up products (not detected in 6 items), up to 0.0029% in face make-up products (not detected in 3 items) and up to 0.0003% in all other cosmetic products (not detected in 17 items), respectively. According to the nickel content from monitoring data and HT25 value of 0.188 mg/kg/day, the life time cancer risk was evaluated for nickel in cosmetic products as 3.0 x 10-6, which is less than 10-5. Furthermore, the skin sensitization (AEL/CEL) was calculated as 1.1 by using EC3 value of 2.5%, which is greater than 1. However, considering the differences in formulations and deviation between products, which can unintentionally contain nickel in marketed cosmetic products, 0.003% for color cosmetic products excluding eye makeup products and 0.001% for other cosmetic products were set as limitation. In case of eye makeup products, the nickel was limited by 0.0035% so that there is less concern for consumers.
학위논문(박사)--아주대학교 일반대학원 :약학과,2018. 8
Keywords: nickel; volatile organic compounds